2013
DOI: 10.1186/2049-6958-8-44
|View full text |Cite
|
Sign up to set email alerts
|

Expiratory CT scan in patients with normal inspiratory CT scan: a finding of obliterative bronchiolitis and other causes of bronchiolar obstruction

Abstract: Expiratory CT scan is usually obtained as supplement to normal inspiratory CT scan to recognize air-trapping, which is expression of small airways obstruction. In some patients the air-trapping may be the only sign of an early-stage small airways disease in an otherwise normal lung.The purpose of this article is to illustrate pathologic conditions, namely obliterative bronchiolitis, in which expiratory CT scan can be abnormal despite normal inspiratory CT examination, and to highlight indications for this tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…In addition, for the mDIXON sequence measurements, cardiac parameters were unaffected by the respiratory phase, although the pulmonary parameters were of course higher in the end‐inspiratory phase than in the end‐expiratory phase. These results are supported by previous studies; indeed, it has been demonstrated that both inspiratory and expiratory CT have great impacts on the evaluation of thoracic movements . Albertal et al showed that assessment of PE at end‐expiration led to an additional number of surgical candidates compared with end‐inspiration assessment.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…In addition, for the mDIXON sequence measurements, cardiac parameters were unaffected by the respiratory phase, although the pulmonary parameters were of course higher in the end‐inspiratory phase than in the end‐expiratory phase. These results are supported by previous studies; indeed, it has been demonstrated that both inspiratory and expiratory CT have great impacts on the evaluation of thoracic movements . Albertal et al showed that assessment of PE at end‐expiration led to an additional number of surgical candidates compared with end‐inspiration assessment.…”
Section: Discussionsupporting
confidence: 78%
“…These results are supported by previous studies; indeed, it has been demonstrated that both inspiratory and expiratory CT have great impacts on the evaluation of thoracic movements. 10 Although the findings of the present study are encouraging, there are still several limitations to this study. First, the sample size was relatively small, and the children were all of school age (> 6 years old).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…While many conditions involve a combination of large and small airways disease, the lung transplant population is distinct in that large airway (anastomotic) or small airway (bronchiolar) complications may occur in isolation of each other; therefore, the inclusion of expiratory views on a CT scan is of particular value in diagnosing and differentiating between these conditions. In bronchiolitis obliterans, expiratory obstruction appears patchy with scattered mosaic air trapping 1. Air trapping confined to certain lobes of the lung without a diffuse nature, as in this case is indicative of an anastomotic complication.…”
Section: Descriptionmentioning
confidence: 65%